Assessment of crosslink network and network defects of unfilled and filled ethylene-propylene-diene terpolymer using solid state nuclear magnetic relaxation spectroscopy - Thanisararat Saleesung (2018)
© 2016 Wiley Periodicals, Inc. Reinforced rubbers are complex compared to unfilled systems. There are differences in the mechanisms affecting network molecular structure as well as properties of the rubber materials. In this article investigation of crosslink network and untied network defects on a molecular level of unfilled and carbon black filled ethylene-propylene-diene terpolymer was carried out using proton solid-state double-quantum NMR spectroscopy. The results show that the filled system demonstrates lower cure efficiency in conjunction with more noncoupled network defects than the unfilled one. In addition, the filled system yields the greater spatial heterogeneity because of the localization of the free radicals at the rubber–filler boundary. These strongly influence the mechanical properties of the filled rubber. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2017, 134, 44224.